The effect of temperature on self-etching adhesive penetration. - Sundfeld, Renato Herman [UNESP]; da Silva, Adriana Maria Jorge Dalácqua; Croll, Theodore P; de Oliveira, Carlos Henrique; Briso, André Luiz Fraga [UNESP]; de Alexandre, Rodrigo Sversut; Sundefeld, Maria Lúcia Marçal Mazza [UNESP] (My University, 2006)
The purpose of this study was to investigate the penetration of an aggressive self-etching adhesive system at refrigerated and room temperatures into ground and unground enamel surfaces. Thirty extracted human teeth were used to measure adhesive penetration into enamel by light microscopy analysis (x400). The unground enamel surfaces were cleaned with pumice and water using a rotary dental brush. For each specimen, part of the unground enamel was manually ground and part was kept intact. A self-etch adhesive was evaluated for its ability to penetrate ground and unground enamel surfaces at room temperature (25 degrees C), at 30 minutes after removal from the refrigerator, and immediately after removal from the refrigerator (6 degrees C). Data were analyzed using variance and the Tukey test, which revealed significant differences in length of penetration of this material when applied on ground and unground enamel surfaces and between the different temperatures used (P > .05). The self-etching system used in this study had significantly lower penetration into unground enamel and at 6 degrees C (P < .05). No statistical difference was found between the interactions of these factors. It was concluded that the self-etching system produced the best penetration into ground enamel surface at room temperature (25 degrees C) and at 30 minutes after removing the specimens from the refrigerator.
Keywords: Prompt L Pop; Prompt L-Pop; resin cement; adolescent; adult; analysis of variance; dental acid etching; dental bonding; human; methodology; surface property; temperature; tooth permeability; Acid Etching, Dental; Adolescent; Adult; Analysis of Variance; Dental Bonding; Dental Enamel Permeability; Humans; Resin Cements; Surface Properties; Temperature